2022
DOI: 10.1088/1361-6463/ac71e2
|View full text |Cite
|
Sign up to set email alerts
|

An epitaxial perovskite as a compact neuristor: electrical self-oscillations in TbMnO3 thin films

Abstract: Developing materials that can lead to compact versions of artificial neurons (neuristors) and synapses (memristors) is the main aspiration of the nascent neuromorphic materials research field. Oscillating circuits are interesting as neuristors, as they emulate the firing of action potentials. Here we present room-temperature self-oscillating devices fabricated from epitaxial thin films of semiconducting TbMnO3. We show that the Negative Differential Resistance (NDR) regime observed in these devices, orginates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 88 publications
1
6
1
Order By: Relevance
“…These curves show a non-linear dependence of frequency with voltage. Although our experiments did not reflect this non-linearity clearly, it was observed experimentally in other threshold memristor systems …”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…These curves show a non-linear dependence of frequency with voltage. Although our experiments did not reflect this non-linearity clearly, it was observed experimentally in other threshold memristor systems …”
Section: Resultscontrasting
confidence: 71%
“…Although our experiments did not reflect this non-linearity clearly, it was observed experimentally in other threshold memristor systems. 43 The non-dependence of current oscillation amplitude on the applied voltage was also observed experimentally by us as well as other researchers on different Mott insulating systems. 35 However, unlike previous models, our simple electrothermal model precisely captures this behavior (further explanation is furnished in section D of Supporting Information, Figures S5 and S6).…”
Section: Characteristics and Salient Features Of Self-oscillationssupporting
confidence: 72%
“…The Sshape or the current-controlled NDR is generally based on impact ionization, filamentary conduction generated by the local phase change or soft breakdown. [14] The IV characteristics shown here belong to the second type, the voltage controlled negative resistance, generating an N-type IV characteristics. [15] This type of NDR is usually produced in classical bulk semiconductors by a transferred-electron effect or in special quantum tunnel devices such as Esaki or resonant tunneling diodes.…”
Section: Resultsmentioning
confidence: 99%
“…The S‐shape or the current‐controlled NDR is generally based on impact ionization, filamentary conduction generated by the local phase change or soft breakdown. [ 14 ]…”
Section: Resultsmentioning
confidence: 99%
“…While a LWIR detector utilizing the NDR of PCM in conjunction with FM-based detection has yet to be reported, prior research has demonstrated the successful creation of self-oscillators with NDR using various PCM, such as metal oxides and 2D materials. [26][27][28][29] Consequently, for the purpose of presenting a general detection scheme, we use the terms PCM and VO 2 interchangeably in the following description. Our room-temperature LWIR detector exhibits a noise equivalent power (NEP) of less than 3 pW • Hz −1/2 , response time ≈2.96 ms and a high detectivity of the order of 10 9 comparable to cryogenically cooled LWIR detectors.…”
Section: Introductionmentioning
confidence: 99%